Working cotton - Williams, Sherley Anne, 1944-1999.; Byard, Carole, 1941-2017 (San Diego : Harcourt Brace Jovanovich, 1992)
A young black girl relates the daily events of her family's migrant life in the cotton fields of central California.
"The text of Working Cotton is based on the poems "the trimming of the feathers" and "conejo, " originally published in The Peacock poems by Sherley Anne Williams"--T.p. verso.
Keywords: Migrant labor -- Fiction; Cotton picking -- Fiction; Families -- Fiction; African Americans -- Fiction